2018
DOI: 10.1159/000492687
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β-Mediated Up-Regulation of WT1D via miR-144-3p and Their Synergistic Effect with NF-κB/COX-2/HIF-1α Pathway on Cell Proliferation in LUAD

Abstract: Background/Aims: IL-1β is an important mediator of “inflammation-cancer" transformation through IL-1β/NF-κB/COX-2/HIF-1α signaling pathway, whereas certain portion of patients with lung adenocarcinoma (LUAD) still suffer from rapid tumor progression in clinical practice, indicating the occurrence of potential bypass. Methods: Real-time polymerase chain reaction was applied to examine the expressions of mir-144-3p, WT1, NF-κB, COX2 and HIF-1α at the mRNA level in 127 LUAD samples and corresponding adjacent tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Multiple experiments in vitro and vivo have shown that IL-1β has a tumor-promoting effect and can promote lung cancer metastasis through adhesion, invasion, and tumor angiogenesis of lung cancer cells. 24 …”
Section: Introductionmentioning
confidence: 99%
“…Multiple experiments in vitro and vivo have shown that IL-1β has a tumor-promoting effect and can promote lung cancer metastasis through adhesion, invasion, and tumor angiogenesis of lung cancer cells. 24 …”
Section: Introductionmentioning
confidence: 99%
“…In terms of histology, there are two types of LC: Non-small cell LC (NSCLC) and small cell LC, of which the former makes up 85% of all cases (4). NSCLC is comprised of two subtypes: Lung squamous cell carcinoma (LUSC) and lung adenocarcinoma (LUAD) (3,5). Drugs targeting mutated versions of the epidermal growth factor receptor (EGFR), GTPase KRas and ALK tyrosine kinase receptor proteins mutations have already demonstrated beneficial effects in patients with LUAD (6).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NF‐κB is closed with the inflammatory response through interleukin (IL)‐1β production (Wu et al, ; Yang et al, ), including ovarian grannulosa cells (Yang et al, ). Some reports demonstrated NF‐κB was expressed in human granulosa luteal cells and activated by TNF‐α, resulting in degradation of IκBalpha and mobilization of NF‐κB into the nucleus (Gonzalez‐Navarrete et al, ), and NF‐κB was also involved in the regulation of rat luteal function as a survival factor and inhibitor of 20alpha‐hydroxysteroid dehydrogenase (Telleria et al, ).…”
Section: Discussionmentioning
confidence: 99%